2006
DOI: 10.1111/j.1532-950x.2006.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometry of Fragmented Medial Coronoid Process in Dogs: A Comparison of Affected and Normal Coronoid Processes

Abstract: Accumulation of fatigue microdamage in the MCP is important in the pathogenesis of FMCP. The underlying cause of this microdamage accumulation must be identified before treatment plans that will prevent further osteoarthritis of the elbow joint can be designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 25 publications
10
119
2
Order By: Relevance
“…Histomorphometry of excised portions of the MCP collected from dogs in our study revealed presence of pervasive subchondral microcracks 22 which supports the theoretical advantage of removing a larger portion of the MCP than that identified as grossly diseased by arthroscopic or CT examination. However, clinical outcomes measures are critical to support application of this hypothesis.…”
Section: Rationale For Scosupporting
confidence: 67%
“…Histomorphometry of excised portions of the MCP collected from dogs in our study revealed presence of pervasive subchondral microcracks 22 which supports the theoretical advantage of removing a larger portion of the MCP than that identified as grossly diseased by arthroscopic or CT examination. However, clinical outcomes measures are critical to support application of this hypothesis.…”
Section: Rationale For Scosupporting
confidence: 67%
“…Danielson's study, 6 medial coronoid specimens from all age groups had diffuse microcrack formation. This finding lends credence to the concept that sudden fragmentation, even in mature dogs is preceded by microcrack formation.…”
Section: Disease Developmentmentioning
confidence: 89%
“…6 These changes typically occur at one of two anatomic sites, either the craniodistal tip of the medial aspect of the coronoid process, or more axially oriented in the region of the radial incisure. Although the precise nature of this fatigue phenomenon remains elusive, several hypotheses encompass the disparate range of recognized pathologic changes, all of which may be attributable to some form of humeroulnar conflict (HUC).…”
Section: Etiopathogenesismentioning
confidence: 99%
See 2 more Smart Citations